Numerasi Siswa SMP dalam Menyelesaikan Soal Setara Asesmen Kompetensi Minimum (AKM) Ditinjau dari Self-Efficacy - Nur Sa'adah Asih; Ika Kurniasari (MATHEdunesa, 2026)
Numeracy plays an important role in developing problem-solving and decision-making skills in various life situations. However, the 2022 national AKM report shows that Indonesian students' numeracy achievement remains relatively low, particularly at the junior high school level. Numeracy can be influenced by psychological aspects, including self-efficacy. This study is descriptive qualitative research that aims to describe junior high school students’ numeracy in solving AKM-like problems based on their level of self-efficacy. The subjects were two eighth-grade students with high mathematical ability: one with high self-efficacy and one with low self-efficacy. The instruments used included a TKA sheet, self-efficacy questionnaire, numeracy test sheet, and interview guidelines. The data from numeracy tests and interviews were analyzed based on three numeracy indicators using the three stages of qualitative data analysis: data reduction, data presentation, and conclusion drawing. The results of the study show that both the high and low self-efficacy subjects met two numeracy indicators: using various types of numbers or mathematical symbols to solve real-life problems and analyzing information presented in different forms (graphs, tables, diagrams, charts, or others). However, unlike the high self-efficacy subject, the low self-efficacy subject did not meet the indicator of interpreting the results of the analysis to predict and make decisions. In solving problems, the student with high self-efficacy tended to be more persistent and did not give up easily, thus successfully finding solutions. In contrast, the low self-efficacy student was more likely to give up when facing difficulties, resulting in failure to solve the problems.